Application of Immunofluorescence to Studies on the Ecology of Sphaerophorus necrophorus - Garcia, M. M. (1971)
Sphaerophorus necrophorus (bovine liver abscess isolates) antiserum was fractionated and labeled with fluorescein isothiocyanate. The fluorescent-antibody (FA) conjugate proved to be species-specific and facilitated the detection of S. necrophorus cells in liver abscesses, viscera, and ruminal contents of cattle. Brightly fluorescing S. necrophorus cells were observed in experimentally inoculated soil incubated anaerobically at 37 and 4 C for 8 and 10 months, respectively. When incubated under moist conditions (80% water holding capacity) at 37 C, the test organism survived in both sterile and unsterile soil for as long as 8 weeks. Results strongly support the feasibility of using FA techniques concurrent with cultural methods for rapid detection of S. necrophorus infections.